2010
DOI: 10.1155/2010/671401
|View full text |Cite
|
Sign up to set email alerts
|

Brandt Extensions and Primitive Topological Inverse Semigroups

Abstract: We study countably compact and absolutely H-closed primitive topological inverse semigroups. We describe the structure of compact and countably compact primitive topological inverse semigroups and show that any countably compact primitive topological inverse semigroup embeds into a compact primitive topological inverse semigroup.In this paper all spaces are Hausdorff. A semigroup is a nonempty set with a binary associative operation. A semigroup S is called inverse if for any x ∈ S there exists a unique y ∈ S … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Also, [17] contains a description of a base of the topology of a primitive Hausdorff feebly compact topological inverse semigroup. Similar results for primitive Hausdorff countably compact topological inverse semigroups and Hausdorff compact topological inverse semigroups were obtained in [7].…”
Section: If X = 0 Then There Exist An Open Neighbourhood W ⊂ G Of Thesupporting
confidence: 81%
See 1 more Smart Citation
“…Also, [17] contains a description of a base of the topology of a primitive Hausdorff feebly compact topological inverse semigroup. Similar results for primitive Hausdorff countably compact topological inverse semigroups and Hausdorff compact topological inverse semigroups were obtained in [7].…”
Section: If X = 0 Then There Exist An Open Neighbourhood W ⊂ G Of Thesupporting
confidence: 81%
“…In the paper [7] the structure of compact and countably compact primitive topological inverse semigroups was described and was shown that any countably compact primitive topological inverse semigroup embeds into a compact primitive topological inverse semigroup.…”
Section: Introductionmentioning
confidence: 99%
“…The constructed example gives a negative answer to Question 17 from [40]. Hclosed and absolutely H-closed (semi)topological semigroups and their extensions in different classes of topological and semitopological semigroups were studied in [8,18,19,[21][22][23][24][25][26] In [6] we showed that the λ-polycyclic monoid for an infinite cardinal λ 2 has similar algebraic properties to that of the polycyclic monoid P n with finitely many n 2 generators. In particular we proved that for every infinite cardinal λ the polycyclic monoid P λ is congruencefree, combinatorial, 0-bisimple, 0-E-unitary, inverse semigroup.…”
Section: ])mentioning
confidence: 99%
“…. Then by Proposition 12 from [2], U(0) is an open-and-closed subset of S. Thus we have that the map f : S → [0, 1] defined by the formula…”
Section: Primitive Pseudocompact Topological Inverse Semigroupsmentioning
confidence: 94%